2016
DOI: 10.7717/peerj.1768
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic gene expression profiles during postnatal development of porcine subcutaneous adipose

Abstract: A better understanding of the control of lipogenesis is of critical importance for both human and animal physiology. This requires a better knowledge of the changes of gene expression during the process of adipose tissue development. Thus, the objective of the current study was to determine the effects of development on subcutaneous adipose tissue gene expression in growing and adult pigs. Here, we present a comprehensive investigation of mRNA transcriptomes in porcine subcutaneous adipose tissue across four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…It has been surveyed that fat mass will be augmented in response to excess caloric intake leading to obesity and further to inflammatory signaling [29]. As part of the immune system, adipose tissue had been identified to be involved in inflammatory response which also inversely participated in obesity and insulin resistance [30]. GO terms, included “leukocyte migration,” “activation of immune response,” and “macrophage differentiation,” were enriched by upregulated DEGs (Figure 3 and Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…It has been surveyed that fat mass will be augmented in response to excess caloric intake leading to obesity and further to inflammatory signaling [29]. As part of the immune system, adipose tissue had been identified to be involved in inflammatory response which also inversely participated in obesity and insulin resistance [30]. GO terms, included “leukocyte migration,” “activation of immune response,” and “macrophage differentiation,” were enriched by upregulated DEGs (Figure 3 and Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, ATP6 could be the key enzyme involved in ATP production during antler development, whereas ATP8 may take over the roles of ATP6 in red deer. In addition, ATP8 , which plays important roles in lipogenesis, was found during the stage of porcine adipose tissue development (Zhang et al, 2016). Weiss et al (2012) reported that ATP8 mutation led to mitochondrial ROS generation with dysregulation of mitochondrial OxPhos system.…”
Section: Discussionmentioning
confidence: 99%
“…In this current study, we used the commonly used method (ANOVA) to identify the differentially expressed mRNAs, lncRNAs and circRNAs during heart differentiation ( Yu et al, 2014 ; Zhang et al, 2016 ). There are a number of statistical tests specifically designed for RNA-Seq data, such as DESeq ( Love et al, 2014 ) and edgeR ( Robinson et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%